Content Analysis of The Textbook For Teaching Arabic in Class Five Primary School in Indonesia/ تحليل المحتوى للكتاب المدرسي لنعليم اللغة العربية في الفصل الخامس من المرحلة الابتدائية بإندونيسيا - M. Robiatul Adawiyah (State Islamic University (UIN) of Sunan Ampel Surabaya, Indonesia, 2021)
Abstract Textbooks are a tool used by teachers or instructors in assisting the implementation of teaching and learning activities in schools. This research was conducted with the aim to find out the quality of Arabic textbooks with the title I Love Arabic for the 5th-grade madrasah by Sunaryo Putro published by the triad as a textbook used in Ibtidaiyah madrasas based on the preparation theory which includes selection, gradation, presentation and reps. This research is classified into library research using the content analysis method. Based on the results of the study showed that the book has met the criteria for the preparation theory which includes good material coverage, and supporting material, in terms of selection has met the criteria and the preparation has been in accordance with the objectives, level of expertise and duration of an Arabic language learning program.